2006
DOI: 10.1590/s0004-28032006000400010
|View full text |Cite
|
Sign up to set email alerts
|

Dispepsia funcional e depressão como fator associado

Abstract: RESUMO ARQGA/1254 INTRODUÇÃOA dispepsia divide-se em dois grandes grupos: um secundário, a doença orgânica, e outro denominado dispepsia funcional (DF). A dispepsia orgânica (DO) pode ser defi nida como a secundária a lesões específi cas, como úlcera péptica, esofagite, câncer gástrico e colelitíase. Assim, é um agrupamento de sintomas resultantes de distintas doenças, sendo estudada a partir das mesmas (21) .No que se refere ao diagnóstico da DF, a falta de uniformidade em relação à defi nição motivou a reali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 27 publications
0
5
0
4
Order By: Relevance
“…18 A study conducted in FD patients found that a coexistent anxiety disorder existed in 28.5% patients, 16 while another study evaluating FD patients at a tertiary outpatient clinic found that 30.4% had a comorbid depression disorder. 17 In FM, the prevalence of an anxiety disorder ranged between 20% and 80% and the prevalence of depression ranged between 13% and 63.8%. 19 Furthermore, one survey study found that 57% of FM patients reported symptoms of posttraumatic stress disorder (PTSD).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 A study conducted in FD patients found that a coexistent anxiety disorder existed in 28.5% patients, 16 while another study evaluating FD patients at a tertiary outpatient clinic found that 30.4% had a comorbid depression disorder. 17 In FM, the prevalence of an anxiety disorder ranged between 20% and 80% and the prevalence of depression ranged between 13% and 63.8%. 19 Furthermore, one survey study found that 57% of FM patients reported symptoms of posttraumatic stress disorder (PTSD).…”
Section: Introductionmentioning
confidence: 99%
“…Depression, anxiety, and other psychiatric comorbidities can frequently coexist with these functional syndromes particularly in more severe cases, although the prevalence can vary among studies (Table 2). 16,17 A study conducted in the Netherlands noted that 30% of Rome II positive IBS patients had anxiety symptoms and 22% had depression symptoms based on the Hospital Anxiety and Depression (HAD) Scale. 18 A study conducted in FD patients found that a coexistent anxiety disorder existed in 28.5% patients, 16 while another study evaluating FD patients at a tertiary outpatient clinic found that 30.4% had a comorbid depression disorder.…”
Section: Introductionmentioning
confidence: 99%
“…Besides this, the intense rhythm associated with chasing productivity and the absence of work breaks is a factor which, when present in the rural work environment, contributes to the appearance of musculoskeletal illnesses (6) .…”
Section: Discussionmentioning
confidence: 99%
“…Some studies identify the environmental conditions of rural work, in particular the dusts arising from organic and mineral sources, as associated with the increase in the prevalence of respiratory illnesses among the workers (6,14) . (8) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation